Permohonan Pemutusan Hubungan Kerja oleh Pekerja/Buruh Karena Dirumahkan Tanpa Upah Lebih dari Tiga Bulan (Analisis Putusan Nomor: 398/Pdt.Sus-PHI/2021/PN. JKT. PST): (Analysis Verdict Number : 398/Pdt.Sus-PHI/2021/PN. JKT. PST ) - Hermanto, joni; Rumainur, Rumainur (UNES Law Review, 2023)
At the end of 2020, to be precise in November 2020, the government passed Law Number 11 of 2020 concerning Job Creation. Several months later, namely in February 2021, the government stipulated implementing regulations for Law Number 11 of 2020, namely Government Regulation Number 35 of 2020 concerning Specific Time Work Agreements, Outsourcing, Working Time and Rest Time, as well as Termination of Employment Relations. People infected by the COVID-19 outbreak continue to increase every day, and the number of deaths due to the COVID-19 outbreak continues to increase. The Central Government and Regional Governments have issued policies to prevent and overcome the spread of the COVID-19 outbreak, namely by implementing Large-Scale Social Restrictions (PSBB) and Implementing Community Activity Restrictions (PPKM). With the implementation of PSBB and PPKM by the government, several sectors, especially the accommodation provision sector, tourism businesses, food and beverage businesses, real estate, and construction experienced direct impacts as a result of the COVID-19 pandemic and the existence of PSBB and PPKM. The tourism sector, especially hotels, experienced a decline in income due to the lack of overnight guests, forcing entrepreneurs to lay off workers without providing wages to reduce expenses and save company finances. This thesis research analyzes the impact caused by laying off workers/laborers without being paid wages and legal considerations regarding the decision of the Industrial Relations Court at the Central Jakarta District Court with case number: 398/Pdt. Sus PHI/2021/PN. JKT. PST. The purpose of this decision analysis is to find out requests for termination of employment (PHK) by workers or employees due to being laid off for more than three months without wages based on Law Number 11 of 2020 concerning Job Creation.